MON-311 Glucose Metabolism in Acromegaly Patients Resistant to First Generation Somatostatin Receptor Ligands Treated with Pegvisomant And/Or Pasireotide Lar - Chiloiro, Sabrina (J Endocr Soc, 2020)
Introduction: Acromegaly (Acro) is a systemic disease characterized by high growth hormone (GH) and insulin like growth factor-I (IGF-I), insulin resistance, glucose intolerance (IGT) and higher diabetes mellitus (DM) risk in 15% - 38% of patients (pts). Moreover, different medical therapies of Acro are reported to have variable effects on glucose metabolism. An association between blood glucose (BG) and serum IGF-I levels in patients with DM and Acro has been suggested, while IGF-I levels and hemoglobin A1c (HbA1c) correlation is still controversial because of the multifactorial influence.Study aim: to investigate glucose metabolism in pts with Acro resistant to 1st gen somatostatin receptor ligands (SRLs) treated with Pegvisomant (Peg) or Pasireotide LAR (Pasi). Patients and Methods: Retrospective, international, multicenter study; consecutive pts enrolled according to following inclusion criteria for at least 6 consecutive months: (1) resistant to 1st gen SRLs, (2) treated with Pasi or Peg for active Acro. Patients with concomitant treatments with known action on glucose metabolism were excluded, with the exception of glucocorticoid replacement for central hypoadrenalism. Results: 72 pts with active Acro, mean age at study entry 37 ±15 yrs, 47 females (65.3%). 28 (38.9%) pts were treated with Pasi and 44 pts with Peg (61.1%). Peg was monotherapy in 18 pts (40.9%) and in combo with first generation SRLs for 26 pts (59.1%). The number of pts with IGT and DM2 was superimposable between the 2 groups (Pasi and Peg). In Pasi group, 19 pts had Acro control (67.9%); glucose metabolism worsened in 16 pts (57.1%). Worsening of glucose metabolism occurred most frequently in pts with persistently active Acro (62.5%) and in pts with higher BG and HbA1c values at study start. Similarly, HbA1c was higher in pts with active Acro, although HbA1c worsened during Pasi treatment both in euglycemic and IGT at study entry, regardless of Acro control. In Peg group, 31 pts reached Acro control (73%); glucose metabolism worsened in 12 (27.3%) but improved in 5 pts (11.4%). All pts who experienced glucose metabolism improvement had controlled Acro, regardless of the use of a combo with first generation SRL. Among the 13 pts with active Acro after Peg, BG worsened in 5 cases (38.4%). Moreover, we found that pts with worsening BG control had higher HbA1c (p=0.03) and required higher Peg doses (mean ±SD 25 ±10 mg/day; p=0.04). Patients with higher HbA1c had higher IGF-I, both at study entry and at study end and were treated with higher Peg dose (mean 25 mg/day). Conclusion: Impaired glucose metabolism was more frequent after Pasireotide treatment and in patients of both Pasireotide and Pegvisomant groups with altered pre-treatment glucose and persistently active disease. Therefore, in such acromegaly patients close monitoring of glucose status is recommended during treatment.